Analysis of Mineral Types, Density, and Porosity in the Lam Teuba Formation Using Infrared Spectroscopy Method - Zahratun; Isa, Muhammad; Sugiyanto, Didik (Jurnal Penelitian Pendidikan IPA, 2024)
The Lam Teuba Formation is one of the local fault areas of the Seulimuem segment located in the Grand Mosque sub-district of Aceh Besar regency. The Lam Teuba Formation has several types of rocks such as basaltic andesite lava, pyrolastic flows, pyroclastic falls, and sedimentary rocks, namely claystone, limestone sandstone, agglomerate, limestone. Rocks have physical characteristics, namely density and porosity which have different values in each rock. This difference can be caused by the minerals contained in the rock. The method used to calculate the density and porosity values used the Archimedes method, and the identification of mineral types using the infrared spectroscopy method. The results of data processing obtained the highest original density value at location 1 sample 1 with a value of 3.42 and the lowest value at location 5 sample 2. The highest dry density value was in location 1 of sample 1 with a value of 3.33 and the lowest value was in location 5 of sample 2. The highest saturation density value was in location 1 of sample 1 with a value of 3.43, the lowest value was in location 5 of sample 2 with a value of 2.07. The average porosity value was the highest with a value of 5.41 in the poor quality category in sample 4, while the lowest value was 4.62 in the very bad category in sample 1. The types of minerals found in the Lam Teuba formation are illite, montmorillonite, kaolinite minerals with a mixture of smectite which is a clay mineral group and siderite minerals which are carbonate mineral groups.